Analisys Of Lead (Pb) And Chromium (Cr) Content In The Roots Of Seagrass (Enhalus Acoroides) In Waters Of Waai And Tulehu Village Central Maluku Regency - Male, Yusthinus T; Sunarti, Sunarti; Nunumete, Neti (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2014)
The research has been done with the aim to determine the content of heavy metals Pb and Cr on the roots of seagrasses (Enhalus acoroides) by using Spektrofotometry Atomic Absorption (SSA). Samples have been taken from the waters of Waai and Tulehu village. The result show that the content of Pb on the roots of seagrasses in the waters of Waai village and Tulehu village is 26,262 mg/Kg; 18,491mg/Kg; 16,272 mg/Kg dan 12,272 mg/Kg. While the content of Cr on the roots of seagrasses in the waters of Waai village ang Tulehu village 33,066 mg/Kg; 7,752 mg/Kg; 109,535 mg/Kg; 22,464 mg/Kg. The result of this study can be used as a reference for the claim that the roots of seagrasses in the Waters of Waai village and Tulehu village contain metals Pb and Cr quite high.